Wewenang Satuan Polisi Pamong Praja Dalam Penegakan Peraturan Daerah - Nikolas Dasem (Kyadiren, 2021)
This study was aimed to investigate the authority of the municipal police to enforce Regional Regulations (Perda) in Biak Numfor Regency and to find out the inhibiting factors in the enforcement of regional regulations. This study uses library research and field research methods which were carried out at the Biak’s municipal police. The author also interviewed respondents and collected data by reviewing literature and decuments related to the research problems. The results obtained from this study include: 1) in enforcing Biak’s Regional Regulation, the municipal Police has a legal basis, namely the rule of national or regional law. The steps taken are guided by the application of Operational Technical Development for Peace and Public Order in collaboration with other law enforcement officials, 2) factors that influence the enforcement of local government regulations are the competence of existing human resources and facilities and infrastructure.